Association between post-stroke cognitive impairment and gut microbiota in patients with ischemic stroke - Tsung-Min Jeng; Yi-Chen Hsieh; Po-Ya Chang; Yu-Ling Li; Sung-Chun Tang; Jiann-Shing Jeng; Chaur-Jong Hu; Hung-Yi Chiou (Scientific Reports)
Abstract More than half of stroke survivors have post-stroke cognitive impairment (PSCI). The role of gut microbiota, which can communicate with the brain through the gut-brain axis and affect inflammation, has been receiving increased attention. This cross-sectional study aimed to investigate the association of PSCI, gut microbiota, and inflammatory markers. Patients with first ischemic stroke and complete 3-month and 1-year follow-up data were included and divided into PSCI and non-PSCI groups according to the Montreal Cognitive Assessment (MoCA) score at the above time points. PSCI was defined as having a MoCA less than 23 at either 3 months or 1 year, or a decrease of more than 2 points at both time points. Gut microbiota was assessed by 16 S rRNA gene sequencing and Next Generation Sequencing analysis. The inflammatory markers included interleukins (ILs), eotaxin, G-CSF, TNF-α, IFNγ, sCD40L, and MCP-1. There were 95 ischemic stroke patients (mean age, 60.5 ± 12.1 years; male, 68.4%), including 30 with PSCI and 65 with non-PSCI. In gut microbiota analysis, the PSCI group had a higher abundance of Bacteroidaceae and Clostridiaceae, and the non-PSCI group had a higher abundance of Prevotellaceae, Ruminococcaceae, Oscillibacter, and Faecalibacterium. Ruminococcaceae family under the Oscillospirales order remains significantly different in the two groups in logistic regression model adjusting confounding variables (p = 0.044). In an analysis of inflammatory markers, the plasma levels of eotaxin (p = 0.041) and IL-12p40 (p = 0.031) were significantly higher in the PSCI group than those in the non-PSCI group, and the plasma level of eotaxin was significantly positively correlated with the amount of Clostridiaceae (rho = 0.389, p = 0.045). The study found that PSCI was associated with certain gut microbiota, and these gut microbiotas correlated with the pro-inflammatory marker eotaxin. This suggests that gut microbiota might play a role in the development of cognitive impairment after ischemic stroke.